S111 Human rhinovirus infection and exacerbation frequency at COPD exacerbation. (14th November 2013) - George, SN; Patel, ARC; Mackay, AJ; Singh, R; Sapsford, RJ; Donaldson, GC; Wedzicha, JA
Abstract : Introduction: Viral infections are associated with more severe COPD exacerbations in terms of greater burden of symptoms, resulting in longer recovery times and a greater likelihood of hospitalisation (Seemungal et al . 2000). Human rhinoviruses (HRV) are the main aetiological agents of virus-associated COPD exacerbations; however the association of HRV infection and exacerbation frequency has not been fully investigated. We aimed to examine the relationship between HRV presence and load, and the number of exacerbations patients experienced per year. Methods: London COPD cohort patients recorded any new or increased respiratory symptoms on daily diary cards and contacted the clinical team when symptoms worsened. Exacerbations were defined using our usual symptomatic criteria; an increase in respiratory symptoms for two consecutive days, with at least one symptom being major (dyspnoea, sputum purulence or volume). Reverse-transcription quantitative PCR was used to detect HRV prevalence and load in sputum samples collected at exacerbation presentation (median 2 days after exacerbation onset). Results: Patients positive for HRV (n = 42) had significantly more exacerbations per year than those without HRV (n = 31); the median (IQR) number of exacerbations per year in those with HRV infection was 3.01 (2.02–5.30) which was significantly greater than those without HRV infection 2.51 (2.00–3.51); p = 0.038 (Figure 1A ). At exacerbation, a higher HRV load significantly correlated with the number of exacerbations patients experienced per year; r = 0.145; p = 0.024 (Figure 1B ). Conclusion: Patients with positive HRV infection at the time of exacerbation had experienced more exacerbations per year than those who did not have HRV. In patients with a higher exacerbation frequency, the HRV load at exacerbation was greater suggesting that patients with a history of frequent exacerbations are more susceptible to viral infection. This susceptibility may provide the mechanisms for the development of the frequent exacerbator phenotype. Thus these findings emphasise the importance of preventing viral infections and exacerbations in COPD patients.